STRUCTURAL EQUATION MODELING DENGAN HUBUNGAN MODERASI PADA PENGARUH TINGKAT INTELEGENSI DENGAN KEBERHASILAN AKADEMIK - Herlawati Herlawati (LPPM Universitas Bina Sarana Informatika, 2011)
Effect of level of intelligence as measured by the ability of logic (KL) and reasoning ability (KP) with academic success (as measured by GPA, there is a possibility that there could interact (measured by the friendliness of (KR) and proximity to the lecturer (KD )) can strengthen or weaken the relationship between the level of intelligence and academic success is. The possibility to interact is the moderating variable. moderating variables are variables that can strengthen or weaken the relationship between independent and dependent variables. Level of intelligence was a direct effect on academic success. Interaction does not directly influence academic success. To examine the relationship between the complex variables that both recursive and non-recursive to obtain the best overall picture of a model used structural equation modeling (SEM) with AMOS software version 16.0 Keywords: Intelligence, GPA, Structural Equation Modeling (SEM), Analysis of Moment Structure (AMOS)